2017
DOI: 10.3390/molecules22060902
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Metabolite Profile in Phyllanthus niruri and Correlation with Bioactivity Elucidated by Nuclear Magnetic Resonance Based Metabolomics

Abstract: Phyllanthus niruri is an important medicinal plant. To standardize the extract and guarantee its maximum benefit, processing methods optimization ought to be amenable and beneficial. Herein, three dried P. niruri samples, air (AD), freeze (FD) and oven (OD), extracted with various ethanol to water ratios (0%, 50%, 70%, 80% and 100%) were evaluated for their metabolite changes using proton nuclear magnetic resonance (1H-NMR)-based metabolomics approach. The amino acids analysis showed that FD P. niruri exhibite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 29 publications
0
18
0
Order By: Relevance
“…The great advancements of sequencing techniques, high-throughput analytical platforms and chemometric Biomolecules 2020, 10, 287 2 of 17 tools that have taken place over the past few decades stood behind the emergence and prosperity of the omics technologies [3]. Recently, metabolomics has become a routine approach in studies aiming to evaluate the activities of medicinal plants or to characterize the metabolites responsible for such activities [4][5][6][7]. Classical methods for determination of the active plant metabolites rely on the activity-guided fractionation and purification techniques.…”
Section: Introductionmentioning
confidence: 99%
“…The great advancements of sequencing techniques, high-throughput analytical platforms and chemometric Biomolecules 2020, 10, 287 2 of 17 tools that have taken place over the past few decades stood behind the emergence and prosperity of the omics technologies [3]. Recently, metabolomics has become a routine approach in studies aiming to evaluate the activities of medicinal plants or to characterize the metabolites responsible for such activities [4][5][6][7]. Classical methods for determination of the active plant metabolites rely on the activity-guided fractionation and purification techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, attentions are being paid on the bioactivities and functional metabolites present in food plants, in addition to their nutritional importance. Metabolomics and chemometric study has been applied recently for identification of bioactive components in plants and plant products (Maree, Kamatou, Gibbons, Viljoen, & Vuuren, ; Mediani et al, ; Yuliana, Budijanto, Verpoorte, & Choi, ) including food plants such as Achras sapota (Das et al, ), Morus alba (Yuliana, Rosa, Budijanto, Verpoorte, & Choi, ), grapes (Ali et al, ), and red wine (Ali et al, ). In this paper, chemometric study revealed identification of a number of metabolites showing β‐glucuronidase inhibitory activities from P .…”
Section: Resultsmentioning
confidence: 99%
“…PCA and PLS-DA were used to evaluate the variations of the two types of wuweizi according to the contents of the 15 components. PCA is an unsupervised pattern recognition method used for analyzing, classifying, and reducing the dimensionality of numerical datasets in a multivariate problem [20,21], and it has been widely used for the quality control of herbal medicines [22,23,24]. PLS-DA is good for highlighting the differences between two groups.…”
Section: Methodsmentioning
confidence: 99%